INTEGRATING DUOLINGO ENGLISH TEST (FREE PRACTICE) IN EFL SPEAKING INSTRUCTION: A QUASI-EXPERIMENTAL STUDY AT UNIVERSITAS NEGERI MEDAN - Tumanggor, Edward Johannes; Annisa, Puan Suri Mira; Syahputri, T. Mira; Br. Bangun, Emia Ninta; Arsita, Dwi Mas; Tambunan, Anastasya Bela Pertiwi (JOURNAL OF LANGUAGE, 2025)
English speaking ability, a primary competency for English Education students, is often hindered by limited practice, lack of confidence, and minimal independent learning media. This study investigates the effectiveness of the Duolingo English Test (Free Practice) platform as a digital learning medium within the Receptive Oral Language Skills course to enhance students' English speaking abilities. This study uses a quantitative approach with a one-group quasi-experimental design, involving a pre-test and post-test to measure improvement before and after the intervention. The intervention consisted of routine practice using the Duolingo platform and supplementary materials from the "Teacher Luke" YouTube channel. Quantitative data from test scores were analyzed using a paired sample t-test, while qualitative data from questionnaires were used to explore student perceptions. The results of this study are expected to provide an effective, flexible learning solution suited for students in the digital era. The conclusion indicates that the strategic use of digital media like the Duolingo English Test can be encouraged in speaking skills instruction at the university level.